The Effect of Yoga on Sleep Quality and Quality of Life in the Elderly: Systematic Literature Review - Arviananda, Hafiya; Djawas, Faizah (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2026)
Background: Sleep disturbances are a common problem among older adults and can reduce quality of life as well as trigger psychological complaints such as stress, anxiety, and depression. Yoga, as a non-pharmacological approach that combines light physical activity, breathing exercises, and relaxation, is considered safe and has the potential to improve sleep patterns and enhance well-being. This study aims to review the effectiveness of yoga exercise on sleep quality and quality of life in older adults. Methods: This study used a systematic literature review method with a search strategy based on the PICO framework and a selection process following PRISMA guidelines. From 521 identified articles, screening based on inclusion and exclusion criteria resulted in 10 articles being included for analysis. Results: The review results indicate that yoga interventions for older adults generally lasted 4–12 weeks with a frequency of 2–6 sessions per week. Overall, yoga was associated with improved sleep quality, reduced psychological complaints, and better quality of life. Discussion: However, variations in intervention methods and outcome measures across studies may limit the comparability of results and the strength of conclusions. Conclusion: Yoga has the potential to be an effective complementary non-pharmacological intervention to improve sleep quality and quality of life in older adults; however, further research with stronger study designs and more standardized protocols is needed to strengthen the evidence.